2010
DOI: 10.1387/ijdb.092874gk
|View full text |Cite
|
Sign up to set email alerts
|

Dicer is required for Sertoli cell function and survival

Abstract: Dicer is a key enzyme that processes microRNA precursors into their mature form, enabling them to regulate gene expression. Dicer null mutants die before gastrulation. To study Dicer function in testis development, we crossed mice carrying a conditional Dicer allele with an AMH-Cre transgenic line, thereby inactivating Dicer in Sertoli cells around embryonic day 14.0 (E14.0). Dicer null Sertoli cells show normal embryonic development, and at postnatal day 0 (P0), testis tubules are normal in number and histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 44 publications
3
56
0
Order By: Relevance
“…In the male germ line, miRNAs are important for the proliferation of primordial germ cells and spermatogonia but are dispensable for the repression of retrotransposons in developing germ cells (62,63). Deletion of Dicer in Sertoli cells causes proliferation and maturation defects and eventually results in failure of germ cell maintenance (62,64,65). All of the above genetic models have illustrated the important roles of DICER-mediated miRNAs in various reproductive tissues.…”
mentioning
confidence: 99%
“…In the male germ line, miRNAs are important for the proliferation of primordial germ cells and spermatogonia but are dispensable for the repression of retrotransposons in developing germ cells (62,63). Deletion of Dicer in Sertoli cells causes proliferation and maturation defects and eventually results in failure of germ cell maintenance (62,64,65). All of the above genetic models have illustrated the important roles of DICER-mediated miRNAs in various reproductive tissues.…”
mentioning
confidence: 99%
“…The dual-fluorescent reporter (Rosa26mTmG) line allows for easy and convenient determination of the onset of Cre activity when crossed with a specific Cre deletor line (Wu et al, 2012). Using this method, we detected Cre activity in Amh-Cre males at ∼E12.5, which is ∼2 days earlier than in an alternative Amh-Cre line (∼E14.5) (Gao et al, 2006;Kim et al, 2010). At E12.5, SC specification has completed and the testis cord has just become morphologically distinguishable.…”
Section: Discussionmentioning
confidence: 99%
“…and small RNA biogenetic factors (e.g. Dicer1) (Sharpe et al, 2003;Nalam et al, 2009;Kim et al, 2010;Matson et al, 2011;Kato et al, 2012). It appears that proper cell fate control during prepubertal SC development involves the precise temporal activation of transcriptional cascades in response to hormonal stimulation (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that Sertoli cells will undergo apoptosis postnatally in mice lacking Sertoli cell expression of Dicer, which is required for micro RNA and small interfering RNA biogenesis (Papaioannou et al ., 2009; Kim et al ., 2010). Sertoli cell apoptosis starts at about postnatal day 3 in these animals although some Sertoli cells survive into adulthood.…”
Section: Sertoli Cellsmentioning
confidence: 99%